PENGEMBANGAN BUKU ILUSTRASI MODIFIKASI PERILAKU ASERTIF: UPAYA PREVENTIF PELECEHAN SEKSUAL PADA ANAK - Andriani, Opi; Zunarti, Rita; Afri Yanti Daulay, Nur (Jurnal Muara Pendidikan, 2024)
The urgency of this research is to reduce the intensity of victims of sexual harassment that occurs in elementary school-age children by increasing assertive behavior through the application of behavior modification modeling techniques by mothers who are guided by illustration books that are specially designed to be easy to understand and apply by family members, especially mothers. This research aims to develop the book "Illustrative Book of Assertive Behavior: Preventive Actions for Sexual Harassment" for parents (mothers) who have elementary school-age children. Researchers used research and development (R&D) research methods with a 4D development model, namely define, design, development, and dissemination. The data analysis technique used is descriptive data analysis technique, namely by describing the validity and practicality of illustrated books. The results obtained from this development research are as follows: (1) The validity of the illustrated book is declared valid in both the material and media aspects (2) The practicality based on the responses of parents and children is declared to be very practical to use. Based on the findings of this research, it is concluded that this illustrated book is valid and practical, so further tests can be carried out to examine the effectiveness of the illustrated book.